Testing research on frequency-dependent characteristics of dynamic stiffness and damping for high-speed railway fastener. (November 2021) - Gao, Xiaogang; Feng, Qingsong; Wang, Anbin; Sheng, Xiaozhen; Cheng, Gong
Abstract: In this paper, the Vossloh W300 fastener currently used in China's high-speed railway is taken as the research object. Combined with the requirements of ISO 10846 series standards and the knowledge of the author, to the best of the authors knowledge, the first high-frequency dynamic stiffness test system for elastic elements of rail fastener has been successfully developed and built. By taking the influence of preloading into consideration, the vertical and lateral dynamic frequency-dependent stiffness and loss factor of high-speed railway W300 fastener at 5~1250 Hz were obtained through the 1:1 test model coupling test method for the first time. Referring to the prediction method of high-speed railway wheel-rail vibration and noise, and factoring in the high-speed rotating, the infinite length of plate track structure and high-speed movement of sound source to wheels, the Kelvin - Voigt simulation sub-model of fastening system was added to predict and analyze the difference between the total sound pressure levels of the wheel and rail that is relative to the standard point under the constant stiffness and frequency-dependent stiffness of fastener. The results indicate that the frequency-dependent characteristics of fastener stiffness have significant impact on the spectrum of wheel-rail interaction forces, total sound pressure levels of rail and wheel-rail. The total sound pressure level of the wheel-rail relative to standard point, which factors in the frequency-dependent stiffness of fastener was approximately reduced 2.6 dB, that is, the frequency-dependent stiffness of fastener can rectify the overestimation of wheel-rail sound pressure level by stiffness coefficient.